Chapter Mapping to prosody Not all parentheticals are alike - Güneş, Güliz (De Gruyter, 2015)
This study investigates the prosody of different types of sentence-medial parentheticals in Turkish. The results of a production experiment show that clausal parentheticals exhibit cues similar to intonation phrase-level cues such as pre-boundary lengthening of the final syllable, longer pauses, and higher final rise. Phrasal parentheticals, on the other hand, exhibit cues similar to phonological phrase-level cues on both edges. From these results, we conclude that clausal parentheticals are prosodically isolated, supporting the theories of syntax-prosody mapping, while XP parentheticals are prosodically integrated, partially supporting syntax-prosody mapping theories. The latter result supports theories that assume XP-to-phonological phrase matching, but not those that predict the prosodic isolation with all parentheticals. In this respect, Turkish marks constituent-to-constituent matching of syntax and prosody more faithfully than the mapping of syntactic isolation. Additionally, mapping of pragmatic information is highly favoured in Turkish. Specifically, pragmatically isolated parentheticals such as vocatives or interjections are prosodically isolated, regardless of their syntactic make-up. We discuss the prosodic structure of Turkish parentheticals and propose a representation that favours the recursion of certain prosodic category types.